Enhancing Biomass-Exopolysaccharides Production of Lignosus rhinocerus in a High-Scale Stirred-Tank Bioreactor and Its Potential Lipid as Bioenergy - Siti Rokhiyah Ahmad Usuldin; Zul Ilham; Adi Ainurzaman Jamaludin; Rahayu Ahmad; Wan Abd Al Qadr Imad Wan-Mohtar (MDPI, 2024)
Indexed by WOS/Scopus/ERA